Recent Studies of Corrosion - Fatigue Crack Growth on the 7081-T73511 Aluminium Alloy - Moreto, Jeferson; Bose Filho, Waldek Wladimir (Orbital: The Electronic Journal of Chemistry, 2023)
This work aims to evaluate the effect of localized corrosion on the fatigue crack growth (FCG) resistance of the 7081-T73511 aluminium alloy. The understanding of this complex combined process was explained by the dissolution of adjacent 7081-T73511 aluminium matrix promoted by the Al7Cu2Fe second-phase particle and the crack tip interaction time with the aggressive medium. Fracture surfaces produced in air and in sea water fog at the testing conditions applied here, basically present the same appearance, with a transgranular, cleavage-like cracking mode for 8